(untitled) (Global Journal of Science Frontier Research, 2018)
In the recent years, to discover knowledge by using data on Internet has become the key research topics. Current researches are taken into account mining and analyzing the specific data including text, images, photos, audio, and video. Most analyzing techniques are focused on data discovering, data mining, big data, and smart algorithm which are based on clustering and artificial intelligent. In this regard, to discover and analyze social media data has become the hottest research topic. In this paper, we study and review some techniques which are used to explore knowledge in the social media data including text mining and discovering, audio and video content analyzing. Based on these techniques, we propose a model and strategies to analyzing social media data and social network management.